Оценка структурно-функциональной значимости элементов в информационных системах экологического мониторинга - Доронина, Ю. В.; Рябовая, В. О. (НТУ "ХПИ", 2014)
В статье рассматривается метод оценки структурно-функциональной значимости элементов информационной системы экологического мониторинга с учетом требований, возникших в процессе её функционирования.

In the article the method of estimation of structural-functional meaningfulness of elements of the ecological monitoring’s system is examined taking into account requirements, in the process of it’s functioning
Estimation of structural-functional meaningfulness of elements is in informative systems of ecological monitoring
Keywords: мониторинговая система; требование к системе; оценка значимости; функциональность; monitoring system; system requirement; estimation of meaningfulness; functionality